A COMPARATIVE CULTURAL STUDY OF GENDER AFFECTED PERCEPTIONS IN MUZAFFARABAD CITY AND QUETTA CITY - Dr. Sumaira Shafiq; Dr. Zainab Akram; Dr. Raja Nazakat Ali (International Journal of Contemporary Issues in Social Sciences, 2023)
This study investigates the perceptions about gender and workouts like aerobics and yoga associated with specific gender group in a multicultural societal setup. This is a comparative analysis on metropolitan cities of Muzaffarabad and Quetta and conducted a survey through questionnaires. The data was collected from randomly selected men and women who regularly visit gyms for health fitness. The findings of the study showed that there seemed no glaring difference of opinion among men and women of two cities about group-based exercises. The men and women of both cities, despite different geographical and cultural scenario, accept the culturally set norms about gendered workouts. It was observed that group exercise like aerobics and yoga are particularly chosen and preferred by women. The group exercise classes are not reported to be arranged for men in both Muzaffarabad and Quetta city due various reasons.